(untitled) (Canadian Medical Education Journal, 2013)
Background: Most universities currently practice traditional practical spot tests to evaluate students. However, traditional methods have several disadvantages. Computer-based examination techniques are becoming more popular among medical educators worldwide. Therefore incorporating the computer interface in practical spot testing is a novel concept that may minimize the shortcomings of traditional methods. Assessing students’ attitudes and perspectives is vital in understanding how students perceive the novel method. Methods: One hundred and sixty medical students were randomly allocated to either a computer-based spot test (n=80) or a traditional spot test (n=80). The students rated their attitudes and perspectives regarding the spot test method soon after the test. The results were described comparatively. Results: Students had higher positive attitudes towards the computer-based practical spot test compared to the traditional spot test. Their recommendations to introduce the novel practical spot test method for future exams and to other universities were statistically significantly higher. Conclusions: The computer-based practical spot test is viewed as more acceptable to students than the traditional spot-test.